STRENGTHENING THE CORE VALUES OF BERAKHLAK IN IMPROVING THE ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF STATE CIVIL APPARATUS - Fahrizal; Juhari; Wargianto; Aklil, Maulan; Tuha, Panca Tuah (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
Employees of the State Civil Apparatus (ASN) must have an extra role in carrying out their functions in serving the community. The relationship between leaders and subordinates in the ASN organization must be able to create a Leader-Member Exchange (LMX) relationship to build a special relationship with enthusiastic employee engagement to achieve the organization's vision and mission based on the Core Values of ASN BerAKHLAK. The research was used a quantitative method to identify the level and nature of the cause-and-effect relationship of the independent Leader-Member Exchange (LMX) and Employee Engagement variables with the dependent variable Organizational Citizenship Behaviour (OCB) and the connecting variable being the core value of AKHLAK. The research population of ASN employees working in the Pangkalpinang City Government is 3505 people, probability sampling while the sampling technique uses simple random sampling, 359 respondents were obtained. Data processing with SmartPLS software version 4.  The Core Values of Morality and employee engagement are key to improving prosocial behaviour (OCB). The important role of Core Value BerAKHLAK as a mediator in the relationship between employee involvement and OCB. Emphasizing the importance of the organization's core values in creating positive performance and behaviour in the workplace. However, the effectiveness of this mediation depends on the extent to which core values are embodied in the organization's culture and supported by an inclusive leadership style. LMX can reinforce an organization's core values. Still, the mediating effect on OCB Insignificance points to the need for a more holistic approach to understanding how leader-subordinate relationships and core values together influence extra-role behaviour.